2019
DOI: 10.1111/jdv.15615
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in kinetochore gene KNSTRN are associated with basal proliferating actinic keratoses and cutaneous squamous cell carcinoma

Abstract: Background Mutations in kinetochore gene KNSTRN accelerate the development of cutaneous squamous cell carcinoma (SCC) and may correlate with different histological classifications of actinic keratosis (AKs). Objective To determine KNSTRN gene mutation frequency in healthy skin (HS), actinically damaged skin (ADS), in AKs with different histomorphological gradings and invasive SCCs. Methods All samples were histologically evaluated. AK lesions were additionally classified according to their upwards (AK I–III) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
(49 reference statements)
0
12
0
3
Order By: Relevance
“…Thus, a mutated KNSTRN gene, especially the p.Ser24Phe mutation, might functionally lead to disrupted chromatid cohesion in normal cells and correlated with increased aneuploidy in primary tumors and enhanced SCC development in vivo (5). Additionally, Schmitz et al recently reported that another recurrent somatic mutation "p.Ala40Glu" in the KNSTRN gene was associated with basal proliferative AK lesions and invasive carcinoma (6). Recent studies also found that altered KNSTRN expression resulted in the loss of chromatid cohesion in the noncutaneous tumor cell line HeLa cells (4,7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a mutated KNSTRN gene, especially the p.Ser24Phe mutation, might functionally lead to disrupted chromatid cohesion in normal cells and correlated with increased aneuploidy in primary tumors and enhanced SCC development in vivo (5). Additionally, Schmitz et al recently reported that another recurrent somatic mutation "p.Ala40Glu" in the KNSTRN gene was associated with basal proliferative AK lesions and invasive carcinoma (6). Recent studies also found that altered KNSTRN expression resulted in the loss of chromatid cohesion in the noncutaneous tumor cell line HeLa cells (4,7).…”
Section: Introductionmentioning
confidence: 99%
“…KNSTRN, an important component of the mitotic spindle, was found to regulate chromosome segregation and anaphase onset during mitosis in cancer cells [72]. Furthermore, recent studies demonstrated that accumulation of KNSTRN mutations may be an early event in cancer development that accelerates tumor growth in cutaneous squamous cell carcinoma and melanoma [73,74]. KIF2C is an important regulator of chromosome segregation, bipolar spindle formation and microtubule depolymerization during mitosis, and it may be related with poor prognosis in non-small cell lung cancer [75].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptose UV-geschädigter Zellen und im Weiteren, durch die Aktivierung von Pro-Onkogenen, zu einem unkontrollierten Wachstum atypischer Keratinozyten [17]. Zusätzlich finden sich UV-induzierte Amplifikationen und aktivierende Mutationen in den Onkogenen HRAS und KNSTRN [18,19].…”
Section: Pathogeneseunclassified